The Idea of Geospatial-Gender-Based Data Infrastructure for Protecting Women Living in Post Covid-19 Created Global Village - Parihar, Seema Mehra; Bannerjee, Tapati; Sonkar, S.; Ali, M. B. (Advances in Social Sciences Research Journal, 2022)
Abstract. The COVID-19 pandemic has altered the lived realities of people across the globe. Though science has made a breakthrough with a vaccine, the virus has already taken the lives of lakhs of people, rendered millions jobless, and taken an emotional toll on the billions world over. Geovisualization with the gendered lens made a world look like a global village with similar pains across regions, class, sexuality, race, and caste. This paper suggests a case for evolving Geospatial-gender-based data Infrastructure (GGBDI) for empowering women. This paper is not only about access to healthcare all over the world but about generating data for empowering women holistically. It also aims to find how gendered the various governments' responses, different institutions, organizations, and families had been. Suggested Geo-Spatial Informatics can assign application developers and users a framework to formulate a comprehensive model on integrating concerns around gender. Paper recognizes the need for putting 300 gender-disaggregated data in one place. The eight thematic GI layers of geospatial data include demography, health and women, economy and livelihood, women violence and safety, education and skill-based opportunities, indigenous communities and women, and gender mainstreaming and budgeting. For each layer and sub-sub layers, using various algorithms, separate GI indexes have been calculated too. Further, around COVID-designed polygons -clusters, buffers, containment zones, the story maps are created with Arc GIS software with the potential of replication. Designed Geospatial informatics aims to be used by planners, policymakers, field functionaries, academicians, and civil societies to collectively and help mainstream gender concerns across policy plans and programs.